Bandwidth, pulse width and wavelength tunability in passively pulse fiber laser / Khalilah Zatiliman Hamdan - Khalilah Zatiliman , Hamdan (2016)
In this study, tunable bandwidth, pulse width and wavelength in passively pulse fiber lasers have been demonstrated and studied. This work consists of 4 experiments where the pulse laser is generated by passive approach using Single-wall carbon nanotube (SWCNT) as saturable absorber. The first experiment, a tunable pulse width in passively mode-locked fiber laser has been realized by varying the length of polarized maintaining fiber (PMF). Bandwidth of mode-locked spectrum is varied and indirectly tunes the pulse width from 0.52 ps to 1.65 ps. The next experiment is on tunable dualwavelengths in passively Q-switched fiber laser. A stable dual-wavelength fiber laser have been demonstrated by using arrayed waveguide grating (AWG) and the wavelength spacing between the two wavelength is switchable from 1.6 nm to 4.0 nm. From this experiment, the repetition rate and pulse width of Q-switched laser obtained changed as the wavelength spacing is varied. Then, the third experiment is on tunable pulse width in passively Q-switched fiber laser. Bandwidth spectrum of the Q-switched laser is tuned by using an ultra-narrow tunable bandpass filter (UNTBF). As the spectral bandwidth is varied the pulse width is also tuned from 2.6 μs to 5.4 μs. The last experiment is on tunable ultra-narrow linewidth passively Q-switched fiber laser. The wavelength spectrum can be tuned from 1525 nm to 1561 nm which is about 37 nm in range by using UNTBF.